Endonuclease-sensitive regions of human spermatozoal chromatin are highly enriched in promoter and CTCF binding sequences - Arpanahi, Ali; Brinkworth, Martin; Iles, David; Krawetz, Stephen A.; Paradowska, Agnieszka; Platts, Adrian E.; Saida, Myriam; Steger, Klaus; Tedder, Philip; Miller, David (Genome Research, 2009)
During the haploid phase of mammalian spermatogenesis, nucleosomal chromatin is ultimately repackaged by small, highly basic protamines to generate an extremely compact, toroidal chromatin architecture that is critical to normal spermatozoal function. In common with several species, however, the human spermatozoon retains a small proportion of its chromatin packaged in nucleosomes. As nucleosomal chromatin in spermatozoa is structurally more open than protamine-packaged chromatin, we considered it likely to be more accessible to exogenously applied endonucleases. Accordingly, we have used this premise to identify a population of endonuclease-sensitive DNA sequences in human and murine spermatozoa. Our results show unequivocally that, in contrast to the endonuclease-resistant sperm chromatin packaged by protamines, regions of increased endonuclease sensitivity are closely associated with gene regulatory regions, including many promoter sequences and sequences recognized by CCCTC-binding factor (CTCF). Similar differential packaging of promoters is observed in the spermatozoal chromatin of both mouse and man. These observations imply the existence of epigenetic marks that distinguish gene regulatory regions in male germ cells and prevent their repackaging by protamines during spermiogenesis. The ontology of genes under the control of endonuclease-sensitive regulatory regions implies a role for this phenomenon in subsequent embryonic development.